IITA-World Bank Establish Regional Hub for Fertilizers and soil Health in West Africa [Set-up and Operationalization of Regional partnership for impact] - Crouch, Jonathan; Vanlauwe, Bernard; Muzata, Barbra (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This report highlights IITA's coordinated efforts toward the establishment of the Regional Hub for Fertilizer and Soil Health, aligned with performance indicator IPI 1.2. It details key milestones achieved, including environmental and social compliance, governance structures, stakeholder engagement, and the official launch, showcasing progress in advancing sustainable soil health and fertilizer management across the region.